2003
DOI: 10.1042/bst0310592
|View full text |Cite
|
Sign up to set email alerts
|

TSC1 and TSC2: genes that are mutated in the human genetic disorder tuberous sclerosis

Abstract: The tuberous sclerosis complex genes TSC1 and TSC2 were first identified by positional cloning strategies in the heritable human disorder tuberous sclerosis. They encode previously unknown proteins, termed hamartin and tuberin respectively, that form a functional complex. The phenotypic manifestations of tuberous sclerosis are extremely diverse and suggest normal roles for TSC1 and TSC2 in regulating the growth, proliferation, migration and differentiation of many cell types. Investigations of TSC1 and TSC2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…One of us (DJK) has also recently confirmed that mosaicism is relatively common among patients with large genomic changes in TSC1 and TSC2 , being seen in 8 of 54 (15%) index patients. However, it appears to be much less common than this for the common small mutations in TSC1 and TSC2 , though the true incidence is uncertain due to mosaicism detection limitations (Verhoef et al, 1995; Kwiatkowska et al, 1999; Dabora et al, 2001; Sampson. 2003; Roberts et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…One of us (DJK) has also recently confirmed that mosaicism is relatively common among patients with large genomic changes in TSC1 and TSC2 , being seen in 8 of 54 (15%) index patients. However, it appears to be much less common than this for the common small mutations in TSC1 and TSC2 , though the true incidence is uncertain due to mosaicism detection limitations (Verhoef et al, 1995; Kwiatkowska et al, 1999; Dabora et al, 2001; Sampson. 2003; Roberts et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As a nutrient sensor, mTORC1 activity fluctuates in vivo in direct response to nutrients, energy status, and growth factor stimulation, which collectively balance cell growth. Complex pathway responses integrate signaling through mTORC1, and disruptions in circuitry signaling can lead to cellular overgrowth and oncogenesis (Inoki et al, 2003;Benvenuto et al, 2000;Sampson, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…2 The ocular, skeletal, gastrointestinal, hepatic, and splenic systems are also frequently affected. 4 Genetic mutations associated with tuberous sclerosis have been mapped to two separate loci containing the genes encoding TSC1/Hamartin and TSC2/Tuberin, 5,6 which collaborate to restrict the activity of the cell growth machinery. Approximately one-third of tuberous sclerosis cases are familial in which one parent is affected.…”
Section: Genetics and Clinical Features Of Tuberous Sclerosismentioning
confidence: 99%